P107 Interferon-induced metabolic perturbations shape the inflammatory status of human monocytes: implications for innovative therapeutic engineering in SLE autoimmunity. (23rd March 2020) - Stathopoulou, Chrysoula; Ntassis, Vasilis; Banos, Aggelos; Gkirtzimanaki, Katerina; Myridakis, Antonis; Adamichou, Christina; Sidiropoulos, Prodromos; Bertsias, George
Abstract : Immune cells have unique metabolic requirements to support the energetic and biosynthetic burden during their activation. Delineation of the metabolic tuning of immune cells could lead to novel strategies in treating metabolically-demanding processes including autoimmune diseases. Among innate effectors, monocytes have a distinct role in systemic lupus erythematosus (SLE) pathogenesis. We have previously described robust type-I interferon (IFNα) signaling in patients with SLE. IFNα-stimulated monocytes from healthy individuals (IFN-Mo) develop mitochondrial hyperpolarization and increased oxidative stress resembling SLE monocytes (SLE-Mo). Here we sought to delineate the metabolic repercussion of IFNα-mediated signaling that could explain metabolic shifts pertaining to autoimmunity. To this end, we combined transcriptomic data with metabolic flux analysis (Seahorse technology) and Gas Chromatography (GC-MS) in healthy monocytes, IFN-Mo and SLE-Mo. Our preliminary results indicate an increased, glucose-dose dependent glycolytic flux in IFNα-treated healthy monocytes recapitulating the SLE-Mo phenotype. Blockade of hexokinase 2 (HK-2)-dependent glycolysis with the use of 2-DG inhibitor attenuated proinflammatory cytokine secretion and the expression of surface markers characteristic of activated monocytes, supporting the deregulated metabolic profile in SLE autoimmunity. Combination of these data with targeted metabolomics (LC-MS) analyses and the application of pathway-specific inhibitors are implemented in vitro to reverse the inflammatory state of SLE monocytes. Together, our data are expected to yield unique insights into the role of immunometabolism in SLE and the potential use of metabolites as novel therapeutic targets in autoimmunity.